Method for constructing metal micro-nano structure element sequence and mechanical property at high flux
By using continuous stiffness method and high-resolution microscopy technology to perform nanoindentation and microstructure analysis in metal materials, the problem that the existing technology cannot achieve multi-dimensional high-throughput characterization in specific areas of the material is solved, and the efficient correlation between the micro-nano structure and mechanical properties of metal materials is achieved and multi-dimensional quantitative characterization is achieved.
Patent Information
- Application Number
- CN202411876325.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing microstructure and mechanical detection technologies cannot achieve multi-dimensional high-throughput quantitative characterization of specific areas of the material, and cannot effectively correlate the micro-nano structure and mechanical properties of the material.
The continuous stiffness method is used to perform high-throughput characterization of the mechanical properties of nanoindentation in specific areas, and field emission scanning electron microscopy of electron backscattering diffraction and energy dispersion spectroscopy system is combined to perform high-resolution microstructure morphology and composition analysis, and a multi-dimensional high-throughput quantitative characterization database is quickly built.
Multi-dimensional high-throughput quantitative characterization of micro-nano-scale tissue composition, structure and mechanical properties in the same area of metal materials is realized, which improves the test resolution and obtains high-precision, shallow indentation and high efficiency results.
Smart Images

Figure CN119643339A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of metal organizational structure and mechanical property characterization methods, and in particular relates to a method for high-throughput construction of metal micro-nano organizational element sequence and mechanical properties. Through multi-dimensional high-throughput characterization of the micro-nano size organizational structure and mechanical properties of metal materials, high-throughput construction of micro-nano organizational structure and mechanical properties in specific areas of metal materials can be achieved. Background Art
[0002] With the development of the times, the requirements for material service performance are becoming more and more stringent, and the development of high-strength and toughness metal structural materials is an eternal theme. Appropriate material testing and characterization methods provide an important basis for exploring the four elements of material composition and structure, synthesis and production process, properties and performance. While the cross-scale multiphase coupling strategy improves the strength and plasticity of materials, it also requires higher analysis and detection of material microstructure and performance, especially when the grain size and reinforcement phase are at the micro-nano scale. The research work on constructing multi-dimensional material testing and characterization methods has attracted much attention. Among the traditional micro-nanostructure and micro-nanomechanical testing technologies that have been developed: micro-nanostructure structure analysis is based on EBSD / EDS rapid characterization; micro-nanomechanical testing is based on discontinuous microindentation characterization, and the test resolution is limited by the size of the indenter. Although the existing microstructure and mechanical testing technologies can realize the testing of the entire or local area of the material, it is impossible to realize the multi-dimensional high-throughput quantitative characterization of the micro-nanostructure and mechanical properties of the same area of the material because it is impossible to extract multi-dimensional characteristic parameters of a specific area of the material. How to establish the correlation between the micro-nanostructure and mechanical properties of the same area of the material through a high-throughput method is of great significance to provide theoretical guidance for the design and preparation of material toughness. Summary of the invention
[0003] In order to solve the above technical problems, the present invention provides a method for high-throughput construction of metal micro-nano organizational element sequence and mechanical properties. On the basis of high-throughput characterization technology of material composition and structure, the continuous stiffness method is used to perform high-throughput characterization of nanoindentation mechanical properties in a specific area, thereby improving the resolution of traditional nanoindentation tests while achieving high precision, shallow indentation and high efficiency; and realizing multi-dimensional high-throughput quantitative corresponding characterization of micro-nanoscale organizational composition, structure and mechanical properties in the same area of metal materials.
[0004] In order to achieve the above object, the present invention adopts the following technical scheme:
[0005] A method for high-throughput construction of metal micro-nano tissue element structure and mechanical properties, comprising the following steps:
[0006] Step 1: Sampling and processing of specific metal areas;
[0007] Step 2: Prepare the analytical test samples to meet the high-throughput test characterization area of composition, structure, and mechanical properties at the micro-nano scale;
[0008] Step 3: Use an indenter equipped with a sensor and a diamond triangular pyramid tip to perform a nanoindentation array experiment on a specific sample area to obtain high-throughput characterization data;
[0009] Step 4: Use a Vickers hardness tester to mark the position coordinates of the nanoindentation mechanical properties high-throughput characterization area that needs to be analyzed and tested;
[0010] Step 5: Use a field emission scanning electron microscope equipped with an electron backscatter diffraction and energy dispersive spectroscopy system to perform high-throughput characterization of the nanoindentation mechanical properties high-throughput characterization area to obtain high-throughput characterization data including high-resolution microstructure morphology, phase, crystal structure and composition analysis;
[0011] Step 6: Process the high-throughput characterization data in steps 3 and 5, and quickly build a multi-dimensional high-throughput quantitative characterization database of the micro-nanostructure and mechanical properties of the same area; establish the relationship between the four elements of material composition, structure, synthesis and production process, properties, and performance one by one.
[0012] Furthermore, the step 1 includes: processing using an ultra-thin sectioning system, wire cutting or a cutting machine according to demand.
[0013] Furthermore, in the step 2, the preparation is achieved by a vibration polisher or an argon ion polisher.
[0014] Furthermore, in the step three, the indentation array experiment is carried out using natural displacement control to control the maximum depth to less than 50 nm, ensuring that the maximum indentation depth of all indentations is consistent; the elastic recovery stage is achieved by rapidly oscillating the tip of the indenter at 150 Hz and proportionally adjusting the oscillation amplitude; and high-throughput characterization of specific areas is obtained, including hardness distribution, modulus distribution, microscopic defects and phase clustering.
[0015] Furthermore, the step six includes: obtaining composition and structural element information of the material from the analysis and testing area, obtaining mechanical property element information using a scanning electron microscope equipped with an electron backscatter diffraction and energy dispersion spectrum system, and guiding the synthesis and production process elements to obtain the elementary sequence of micro-nano tissues and structures with corresponding mechanical properties based on the correspondence between composition, structure and mechanical properties, thereby establishing the relationship between these four elements.
[0016] Beneficial effects:
[0017] 1. Compared with the traditional nanoindentation mechanical properties characterization test method, the present invention uses the continuous stiffness method to perform high-throughput characterization of nanoindentation mechanical properties in a specific area, improving the resolution of traditional nanoindentation testing while achieving high precision, shallow indentation and high efficiency; it can obtain multi-dimensional material mechanical property parameters such as hardness distribution, modulus distribution, microscopic defects and phase clustering in a specific area.
[0018] 2. The present invention utilizes a variety of high-throughput characterization technologies to successfully and rapidly build a multi-dimensional high-throughput quantitative characterization of the micro-nanostructure and mechanical properties of the same area, and realizes the rapid correlation between the four elements of metal materials.
[0019] 3. The present invention is applicable to various metal materials, such as pure Ti metal, steel, high-temperature alloys, high-entropy alloys, amorphous composite materials, etc., and can achieve multi-dimensional high-throughput quantitative characterization of micro-nanostructure and mechanical properties in the same area. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is the high-throughput characterization result of hardness distribution, modulus distribution, H / E and phase clustering in specific area obtained after continuous stiffness method nanoindentation test of aged FeCoNi multi-component alloy sample in step three of Example 1; wherein ad corresponds to the hardness, modulus, hardness / modulus and phase clustering analysis diagrams of the test area, respectively.
[0021] Figure 2 This is a nanoindentation morphology image under an optical microscope after the continuous stiffness method nanoindentation test of the FeCoNi-based multi-component alloy aged sample in step 4 of Example 1.
[0022] Figure 3 This is the result of SEM and composition analysis of the nanoindentation area in step 3 after the continuous stiffness method nanoindentation test of the aged FeCoNi multi-component alloy sample in step 5 of Example 1. Among them, a is the microstructure morphology image of the test area taken by a scanning electron microscope (SEM), and bd corresponds to the distribution of the three elements Fe, Ni and Al in the test area.
[0023] Figure 4 After the continuous stiffness method nanoindentation test of the aged FeCoNi multi-component alloy sample in step 5 of Example 1, the EBSD result map of the nanoindentation area in step 3 is performed. Among them, ad corresponds to the grain boundary distribution map, crystal orientation anti-pole figure, grain map and phase distribution map of the test area respectively.
[0024] Figure 5It is the high-throughput characterization result of hardness distribution, modulus distribution, H / E and phase clustering in a specific area obtained after continuous stiffness method nanoindentation test of 304 stainless steel sample in step 3 of Example 2. Among them, ad corresponds to the hardness, modulus, hardness / modulus and phase clustering analysis diagram of the test area respectively.
[0025] Figure 6 This is the nanoindentation SEM morphology image of the 304 stainless steel sample after the continuous stiffness method nanoindentation test in step 4 of Example 2.
[0026] Figure 7 This is the EBSD result diagram of the nanoindentation area in step 3 after the continuous stiffness method nanoindentation test of the 304 stainless steel sample in step 4 of embodiment 2. Wherein, ab corresponds to the image quality and crystal orientation inverse pole figure of the test area respectively. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical solutions and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the accompanying drawings and examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in each embodiment of the present invention described below can be combined with each other as long as they do not conflict with each other. A high-throughput method for building a metal micro-nano structure element sequence and mechanical properties of the present invention comprises the following steps:
[0028] Step 1: Use ultra-thin sectioning system, wire cutting, cutting machine and other methods to sample and process specific areas of metal according to needs;
[0029] Step 2: Use vibration polishers, argon ion polishers and other sample preparation equipment to efficiently prepare the analytical test samples to meet the requirements of high-throughput testing and characterization of composition, structure, and mechanical properties at the micro-nano scale.
[0030] Step 3: Perform nanoindentation array experiments on specific sample areas using the FT-I04Femto indenter equipped with an FT-S20000 sensor and a diamond Berkovich (triangular pyramid) tip. The indentation array experiment was performed using natural displacement control to control the maximum depth to less than 50 nm, ensuring that the maximum indentation depth of all indentations was consistent. The elastic recovery phase was achieved by rapidly oscillating the indenter tip at 150 Hz and proportionally adjusting the oscillation amplitude. This continuous stiffness measurement (CSM) enables the evaluation of stiffness associated with different depths. High-throughput characterization of hardness distribution, modulus distribution, microscopic defects, and phase clustering in specific areas is obtained.
[0031] Step 4: Use a Vickers hardness tester to mark the position coordinates of the nanoindentation mechanical properties high-throughput characterization area that needs to be analyzed and tested;
[0032] Step 5: Use a field emission scanning electron microscope (SEM) equipped with electron backscatter diffraction (EBSD) and energy dispersive spectroscopy (EDS) to perform high-throughput characterization of the nanoindentation mechanical properties in the area of high-throughput characterization of high-resolution microstructure morphology, phase, crystal structure and composition analysis.
[0033] Step 6: Process the multi-dimensional high-throughput test characterization data of specific areas in steps 3 and 5, and quickly build a multi-dimensional high-throughput quantitative characterization database of micro-nanostructure and mechanical properties in the same area. Establish the relationship between the four elements of material composition and structure, synthesis and production process, properties and performance one by one.
[0034] The present invention is further illustrated by the following examples, but is not limited to the following examples.
[0035] Embodiment 1:
[0036] This embodiment provides a method for quickly constructing a multi-dimensional high-throughput quantitative characterization of micro-nanostructure and mechanical properties in the same region in a FeCoNi-based multi-component alloy, which specifically includes the following steps:
[0037] Step 1: According to the needs, use ultra-thin sectioning system, wire cutting, cutting machine and other means to cut characterization samples from the FeCoNi series multi-component alloy aging state test sample.
[0038] Step 2: Metallographic sample preparation is performed on the aged FeCoNi multi-component alloy samples to be tested, including mounting, rough grinding, fine grinding, polishing and other processes; vibration polishing machine, argon ion polishing and other sample preparation equipment are used to efficiently prepare the sample surface that meets the requirements of high-throughput testing and characterization of micro-nanoscale organizational composition, structure and mechanical properties.
[0039] Step 3: Nanoindentation of a specific sample area using an FT-I04 Femto indenter equipped with a FT-S20000 sensor and a diamond Berkovich tip for 50 50 array experiments. The indentation array experiment was performed with natural displacement control, with the maximum depth controlled to be equal to 40 nm. The indentation interval was set to 400 nm to ensure that the maximum indentation depth of all indentations was consistent. The elastic recovery phase was achieved by rapidly oscillating the tip of the indenter at 150 Hz and proportionally adjusting the oscillation amplitude. This continuous stiffness measurement (CSM) enables the assessment of the stiffness associated with different depths. High-throughput characterizations such as hardness distribution, modulus distribution, microscopic defects, and phase clustering in specific areas can be obtained. Figure 1 According to the evolution of H and E distribution, it can be clearly distinguished that the hardness and modulus of different grains are different, and it is observed that the hardness of the second phase distributed along the grain boundary is much higher than that of the matrix phase.
[0040] Step 4: Use a Vickers hardness tester to mark the area of the FeCoNi multi-component alloy aged sample that has completed the continuous stiffness method nanoindentation test characterization, so as to quickly locate the indentation position. The morphology under the nanoindentation optical microscope is as follows: Figure 2 As shown;
[0041] Step 5: Use a field emission scanning electron microscope equipped with EBSD / EDS to perform high-resolution microstructure morphology, phase, crystal structure and composition analysis on the high-throughput characterization area of nanoindentation mechanical properties in step 3. Figure 3 and Figure 4 As shown. Figure 3 and Figure 4 As shown, the second phase enriched in Ni and Al elements precipitates along the grain boundary. The second phase is NiAl phase with a volume fraction of 6%; the matrix is austenite phase.
[0042] Step 6: Process the multi-dimensional high-throughput test characterization data of specific areas in steps 3 and 5, and successfully and quickly build a multi-dimensional high-throughput quantitative characterization database of micro-nanostructure (composition distribution, microstructure morphology, phase distribution, crystal orientation, etc.) and mechanical properties (hardness, modulus, micro-defects and phase clustering, etc.) in the same area. Establish the relationship between the four elements of material composition and structure, synthesis and production process, properties and performance one by one. This embodiment found through high-throughput characterization that the hardness of the second phase precipitated along the grain boundary of the FeCoNi-based multi-component alloy aging state to be tested sample is higher than that of the matrix, and the precipitation morphology and volume fraction both affect the macroscopic properties of the material. The present invention provides theoretical guidance for the design and preparation of material toughening.
[0043] Embodiment 2:
[0044] This embodiment provides a method for quickly constructing a multi-dimensional high-throughput quantitative characterization of micro-nanostructure and mechanical properties in the same area in 304 stainless steel, which specifically includes the following steps:
[0045] Step 1: Cut characterization samples from 304 stainless steel samples using ultra-thin sectioning systems, wire cutting, cutting machines, and other methods as needed.
[0046] Step 2: Perform metallographic sample preparation on the 304 stainless steel sample to be tested, including mounting, rough grinding, fine grinding, polishing and other processes; use vibration polishing machine, argon ion polishing and other sample preparation equipment to efficiently prepare the sample surface that meets the requirements of high-throughput testing and characterization of micro-nanoscale organizational composition, structure and mechanical properties.
[0047] Step 3: Nanoindentation of a specific sample area using an FT-I04 Femto indenter equipped with a FT-S20000 sensor and a diamond Berkovich tip for 50 50 array experiments. The indentation test was performed with natural displacement control, with a maximum depth of 40 nm and an indentation interval of 400 nm to ensure that the maximum indentation depth of all indentations was consistent. The elastic recovery phase was achieved by rapidly oscillating the tip of the indenter at 150 Hz and proportionally adjusting the oscillation amplitude. This continuous stiffness measurement (CSM) enables the assessment of the stiffness associated with different depths. High-throughput characterizations such as hardness distribution, modulus distribution, micro-defects and phase clustering in specific areas can be obtained. Figure 5 According to the evolution of H and E distribution, it can be clearly distinguished that the hardness and modulus of grains with different orientations are different. At the same time, it is observed that the hardness of the twin crystals in the crystal is much higher than that of the matrix phase.
[0048] Step 4: Use a Vickers hardness tester to mark the area of the 304 stainless steel sample that has completed the continuous stiffness method nanoindentation test characterization, so as to quickly locate the indentation position. The nanoindentation SEM morphology is as follows: Figure 6 As shown;
[0049] Step 5: Use a field emission scanning electron microscope equipped with EBSD / EDS to perform high-throughput characterization of the nanoindentation mechanical properties in step 3, such as high-resolution microstructure morphology and crystal structure analysis. Figure 7 shown.
[0050] Step 6: Process the multi-dimensional high-throughput test characterization data of the specific area in step 3 and step 5, and successfully and quickly build a multi-dimensional high-throughput quantitative characterization database of micro-nanostructure (microstructure morphology, crystal orientation, etc.) and mechanical properties (hardness, modulus, micro-defects and phase clustering, etc.) in the same area. Establish the relationship between the four elements of material composition and structure, synthesis and production process, properties and performance one by one. The present invention provides theoretical guidance for the design and preparation of material toughening.
[0051] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for high-throughput construction of metal micro-nanostructure element structure and mechanical properties, characterized in that: The steps include: Step 1: Sampling and processing of specific metal areas; Step 2: Prepare the analytical test samples to meet the high-throughput test characterization area of composition, structure, and mechanical properties at the micro-nano scale; Step 3: Use an indenter equipped with a sensor and a diamond triangular pyramid tip to perform a nanoindentation array experiment on a specific sample area to obtain high-throughput characterization data; Step 4: Use a Vickers hardness tester to mark the position coordinates of the nanoindentation mechanical properties high-throughput characterization area that needs to be analyzed and tested; Step 5: Use a field emission scanning electron microscope equipped with an electron backscatter diffraction and energy dispersive spectroscopy system to perform high-throughput characterization of the nanoindentation mechanical properties high-throughput characterization area to obtain high-throughput characterization data including high-resolution microstructure morphology, phase, crystal structure and composition analysis; Step 6: Process the high-throughput characterization data in steps 3 and 5, and quickly build a multi-dimensional high-throughput quantitative characterization database of the micro-nanostructure and mechanical properties of the same area; establish the relationship between the four elements of material composition, structure, synthesis and production process, properties, and performance one by one.
2. The method for high-throughput construction of metal micro-nanostructure element structure and mechanical properties according to claim 1, characterized in that: The step 1 includes: using an ultra-thin sectioning system, wire cutting or a cutting machine for processing according to needs.
3. The method for high-throughput construction of metal micro-nanostructure element structure and mechanical properties according to claim 1, characterized in that: In the step 2, the preparation is achieved by a vibration polisher or an argon ion polisher.
4. The method for high-throughput construction of metal micro-nanostructure element structure and mechanical properties according to claim 1, characterized in that: In step three, the indentation array experiment is carried out using natural displacement control to control the maximum depth to less than 50 nm, ensuring that the maximum indentation depth of all indentations is consistent; the elastic recovery stage is achieved by rapidly oscillating the tip of the indenter at 150 Hz and proportionally adjusting the oscillation amplitude; and high-throughput characterization of specific areas is obtained, including hardness distribution, modulus distribution, microscopic defects and phase clustering.
5. The method for high-throughput construction of metal micro-nanostructure element structure and mechanical properties according to claim 1, characterized in that: The step six includes: obtaining the composition and structural element information of the material from the analysis and testing area, obtaining the mechanical property element information using a scanning electron microscope equipped with an electron backscatter diffraction and energy dispersion spectrum system, and guiding the synthesis and production process elements to obtain the elementary sequence of micro-nano tissues and structures with corresponding mechanical properties based on the correspondence between the composition, structure and mechanical properties, thereby establishing the relationship between the four elements.
Citation Information
Patent Citations
Statistical distribution analysis mapping characterization method for original material position
CN104535737A
Method for preparing amorphous alloy surface microstructure by coupling technology of pre-indentation and polishing
CN107881508A
Method for quickly representing ceramic-based composite material mechanical property
CN109870476A
Method for constructing surface hardness difference based on non-uniform stress
CN110823735A
Research method of high-flux metal additive manufacturing process parameters
CN111829868A